Mineralizing Coating on 3D Printed Scaffolds for the Promotion of Osseointegration - Hasan, Abshar; Bagnol, Romain; Owen, Robert; Latif, Arsalan; Rostam, Hassan M.; Elsharkawy, Sherif; Rose, Felicity R. A. J.; Rodríguez-Cabello, José Carlos; Ghaemmaghami, Amir M.; Eglin, David; Mata, Alvaro (Frontiers in Bioengineering and Biotechnology, 2022)
Design and fabrication of implants that can perform better than autologous bone grafts remain an unmet challenge for the hard tissue regeneration in craniomaxillofacial applications. Here, we report an integrated approach combining additive manufacturing with supramolecular chemistry to develop acellular mineralizing 3D printed scaffolds for hard tissue regeneration. Our approach relies on an elastin-like recombinamer (ELR) coating designed to trigger and guide the growth of ordered apatite on the surface of 3D printed nylon scaffolds. Three test samples including a) uncoated nylon scaffolds (referred to as ‘Uncoated’), b) ELR coated scaffolds (referred to as ‘ELR only’), and c) ELR coated and in vitro mineralized scaffolds (referred to as ‘Pre-mineralized’) were prepared and tested for in vitro and in vivo performance. All test samples supported normal human immortalized mesenchymal stem cell adhesion, growth, and differentiation with enhanced cell proliferation observed in the ‘Pre-mineralized’ samples. Using a rabbit calvarial in vivo model, ‘Pre-mineralized’ scaffolds also exhibited better bone ingrowth into scaffold pores and cavities with better tissue-implant integration. However, the coated scaffolds (‘ELR only’ and ‘Pre-mineralized’) did not exhibit significantly more new bone formation compared to ‘Uncoated’ scaffolds. Overall, the mineralizing coating offers an opportunity to enhance integration of 3D printed bone implants. However, there is a need to further decipher and tune their immunologic response to develop truly osteoinductive/conductive surfaces.